2010
DOI: 10.1111/j.1467-8624.2010.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami, War, and Cumulative Risk in the Lives of Sri Lankan Schoolchildren

Abstract: This study examines the impact of children's exposure to natural disaster against the backdrop of exposure to other traumatic events and psychosocial risks. One thousand three hundred ninety-eight Sri Lankan children aged 9-15 years were interviewed in 4 cross-sectional studies about exposure to traumatic life events related to the war, the tsunami experience, and family violence. Symptoms of posttraumatic stress disorder, somatic complaints, psychosocial functioning, and teacher reports of school grades serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 37 publications
5
48
0
7
Order By: Relevance
“…Children's more recent experiences of natural disasters are better documented with children increasingly being a primary focus in both disaster relief efforts and in disaster recovery. The impacts of major disasters on children have been identified for a number of recent disasters including the Sri Lankan tsunami (Catani et al 2010;Feranando et al 2010), Hurricane Katrina (Kilmer & Gil-Rivas 2010;Kronenberg et al 2010), the Chinese earthquake in Beichuan (Zeng & Silverstein 2011) and the Japanese earthquake and tsunami (McCurry 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Children's more recent experiences of natural disasters are better documented with children increasingly being a primary focus in both disaster relief efforts and in disaster recovery. The impacts of major disasters on children have been identified for a number of recent disasters including the Sri Lankan tsunami (Catani et al 2010;Feranando et al 2010), Hurricane Katrina (Kilmer & Gil-Rivas 2010;Kronenberg et al 2010), the Chinese earthquake in Beichuan (Zeng & Silverstein 2011) and the Japanese earthquake and tsunami (McCurry 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3 There is a growing consensus that mental health care interventions in post con£ict settings need to be integrated into existing systems (Pe¤ rez-Sales et al, 2011) and that the treatment of mental disorders within the health care systems needs to be accompanied by a community based approach that focuses on psychosocial problems (De Jong & Kleber, 2007;Ventevogel et al, 2012). 4 Our group did research on the general adaptation of children (Catani et al, 2010), family violence and child maltreatment Catani, 2009;Catani et al, 2010), inter-partner violence (Saile et al, 2013), and drug-induced psychosis (Odenwald et al, 2005;Odenwald et al, 2007;Odenwald et al, 2009). 5 Mundt et al (2014) state that there is only one review of NET.…”
Section: Resultsmentioning
confidence: 99%
“…It is of interest that we did not find that children who witnessed the tsunami or were injured reported increased traumatic symptoms, contrary to previous literature 9 . Other research has found a dose effect of trauma exposure, namely increased trauma exposure following a natural disaster to be associated with increased traumatic symptoms 25 . In our sample it is noteworthy that despite over half of the child survivors losing homes and property, children were far more impacted by the loss of a loved one.…”
Section: Discussionmentioning
confidence: 99%